Assessment of Vanes Effectiveness in Controlling Erosion and Deposition Zones at a River Confluence using a 2D model - Ali, Hydar Lafta (International Journal of Integrated Engineering, 2019)
Controlling erosion and deposition zones that are usually forming at rivers confluences are important for improving river hydraulic efficiency. The flow in rivers confluences is highly complex, due to rapid changes associated with the river flow dynamics, sediment transport, and morphology. A two-dimensional (2D) numerical model was used to simulate the confluence between Kurau and Ara rivers, Perak, Malaysia. The numerical model has been calibrated and validated by using field data. The model was used to investigate the effectiveness of different shapes and sizes of 30o obstacles/vanes in controlling erosion and deposition zones at the confluence of Kurau and Ara rivers. The simulation results show that the best performance of 30o obstacles/vanes was found when a single obstacle/vane was introduced in the flow.